Dispersal Propensity and Dispersal Distance Are Genetically Independent Traits in a Stream Salamander - Winsor H. Lowe; Brett R. Addis; Madaline M. Cochrane (Molecular Ecology, 2026)
Empirical understanding of dispersal evolution is limited, due in large part to the complexity of the dispersal process and the difficulty of quantifying dispersal directly. To move ahead, it may help to focus on universal dispersal traits: propensity—the discrete emigration response distinguishing dispersers from non‐dispersers—and distance. In particular, little is known about the evolution of dispersal distance, including whether it is an independent trait subject to selection. We used capture‐recapture data and single nucleotide polymorphism (SNP) genotypes from 1906 salamanders sampled over 10 years to test for independent genetic associations with dispersal propensity and distance. Gyrinophilus porphyriticus is a headwater specialist, and our data are from three hydrologically independent streams in New Hampshire. We quantified dispersal propensities and distances directly with recapture histories and we used principal component analysis of SNP genotypes to derive three orthogonal axes of genetic variation. Of 173 recaptured individuals, 81 were non‐dispersers and 92 were dispersers based on an empirically derived 3‐m threshold distinguishing dispersal from movements within an individual's home range. Dispersal distances ranged from 4 to 1248 m. Dispersal propensity and distance were significantly associated with different axes of genetic variation, indicating that these are independent traits capable of responding to different selective forces. More broadly, these results show that quantifying dispersal propensities and dispersal distances—and explicitly assessing interactions and trade‐offs between these traits—may help to advance understanding of dispersal evolution.